Intracranial extension of choroidal melanoma via the optic nerve. - Shields, C L (1987)
A 62-year-old woman was treated with cyclocryotherapy for neovascular glaucoma of uncertain origin. Fifteen months later she was diagnosed as having a choroidal melanoma, which extended extrasclerally to fill the orbit and invaded the optic nerve intracranially to the chiasm. She was treated by orbital exenteration and neurosurgical resection of the intracranial portion of the optic nerve. The patient is alive and clinically free of metastasis five years after the onset of neovascular glaucoma and almost four years after surgical resection. The significance of this highly unusual growth pattern of uveal melanoma is discussed.